MODERNITAS KYAI DAN IMPLIKASINYA TERHADAP PENDIDIKAN KEWIRAUSAHAAN DI PONDOK PESANTREN - Agus Eko Sujianto (Millah: Journal of Religious Studies, 2011)
This study was developed from the results of in-depth research that aims to explain the contribution modernity of Kyai and their implications for entrepreneurship education in boarding schools (Pontren). The research approach used is a quantitative approach on the Boarding School Cooperatives (Koppontren) in Tulungagung District. The results showed that modernity indicated with the attitudes of Kyai with individual characteristics of modernity can increase the performance of Koppontren. That is, if a Kyai has attitudes and performs activities that lead to the advancement either for himself or other people included Koppontren, the existence of Koppontren can be enjoyed by the members.